Pengaruh Sosial Media Marketing dan Word Of Mouth Terhadap Keputusan Pembelian - Yuyuk Liana (Bulletin of Management and Business, 2021)
The development of information technology at this time has been very rapid, for that it encourages every business actor to come into contact with the world of information technology to support the business carried out. The purpose of this study was to find out the influence of social media marketing on purchasing decisions and the influence of word of mouth on purchasing decisions. The population is a consumer of Dancell Warujayeng which numbers 100 respondents. The method of collecting data is to distribute questionnaires. The results showed that social media marketing has a significant influence on purchasing decisions and word of mouth also has a significant effect on purchasing decisions.